LIQUIDITY AND SOLVABILITY ON PROFITABILITY : A STUDY ON TOLL ROAD SUB -SECTORS COMPANIES LISTED AT INDONESIAN STOCK EXCHANGE - Nababan, Ivan Morgan (Universitas Muhammadiyah Tangerang, 2021)
In the current era of development, Indonesian companies not only have to compete with domestic companies but face diverse competition from abroad. These conditions have also fueled competition in the industry sector. By maintaining and able to develop the companies, and achieving company goals both management and company leaders are often faced with various problems both technical, administrative and financial. Therefore the company management must take rational decisions and can be accounted for and the decision-maker requires a clear picture of the problems faced by the company. If the company increases the amount of debt as a source of funds it can increase financial risk. If the company cannot manage funds raised from debt productively, it can have a negative effect and have an impact on decreasing company profitability. Conversely, if the debt can be managed well and used for productive investment projects, it can have a positive influence and have an impact on increasing the profitability of companies. Investment in infrastructure is considered that it is one of the best ways to develop money. infrastructure has the opportunity to get a large return on investment.Profitability is the company's ability to make a profit concerning sales, total assets, and own capital (Sartono in Ima Hernawati, 2007). High profitability will illustrate the effectiveness of management in managing the company in generating profits. If the effectiveness and efficiency of capital use can be achieved, then there is a possibility that the company will make a large profit. Liquidity is related to the problem of a company's ability to meet its financial obligations that must be met immediately. The amount of payment instruments (liquid instruments) owned by a company at one time is the paying power of the company concerned. A company that has the power to pay may not be able to fulfill all financial obligations that must be fulfilled immediately or in other words the company may not have the ability to pay. The solvency of a company shows the company's ability to meet all financial obligations if the company is currently liquidated. The definition of solvency is intended as the company's ability to pay all its debts, both long-term and long-term. This research is expected to add insight into the effect of liquidity on profitability in other companies on the Indonesia Stock Exchange